Mobile Robot Detects Pests And Diseases In Palm Oil Nurseries - Raden Aris Sugianto; Andi Prayogi; Hasanal Fachri Satia Simbolon (University of Science and Computer Technology, 2024)
The palm oil industry is an important economic pillar in various countries, making a significant contribution to global vegetable oil production. Despite its vital role, oil palm growth is often faced with serious challenges such as pest and disease attacks that can threaten crop yields and plant health. Oil palm seeding, as the initial stage in the plant growth cycle, is key in ensuring optimal quality and productivity in the future. The successful application of mobile robot technology in detecting pests and diseases in oil palm nurseries will not only increase production efficiency, but also support the principles of sustainability and wise resource management.